Manejemen Pengumpulan dan Pendistribusian Dana Zakat, Infak dan Sedekah pada LAZNAS Al-Irsyad Purwokerto - Yusuf Alaika Fawaid (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
This study aims to determine how management is in collecting and distributing ZIS funds and what are the inhibiting and supporting factors in collecting and distributing ZIS funds at LAZNAS Al-Irsyad Purwokerto. This study uses a qualitative method of field research, namely research that is directly in the field or informants. This data source consists of primary and secondary data obtained through observation, interviews and documentation from LAZNAS Al Irsyad Purwokerto. In the analysis of this study using descriptive analysis in which the data is qualitative in nature which is researched, developed, and adapted to the existing supporting theories. This study shows that the collection and distribution of ZIS funds at LAZNAS Al Irsyad Purwokerto goes through 4 stages, namely planning, organizing, implementing and supervising. However, in the stage of organizing and supervising, it is still less than optimal. The obstacles in collecting ZIS funds are that zakat payments can be made independently and there are no institutional barriers, while the supporters are competent administrators, religious obligations and the existence of laws that regulate. The obstacles to its distribution are the obstacles in the distribution of ZIS funds are the lack of Human Resources (HR) and car operations, while supporting it is the existence of a clear program design, the availability of funds, and the number of people who are still under poverty. Keywords: ZIS collection management, ZIS distribution management, LAZNAS Al Irsyad Purwokerto